Odpowiedzi

2009-12-15T17:40:28+01:00
A) dla x=1
y=2x^2 +1
y= 2+1 = 3

dla x= -1
y= 2x^2+1
y= 2+1= 3

b) dla x=1
y= -3x^2
y= -3

dla x= -1
y= -3x^2
y= -3 <---- -1 do kwadratu daje 1 na plusie mamy minus przy 3 więc taki wynik

c) dla x= 1
y= -3/x
y= -3/1= -3

dla x= -1
y= -3/x
y= -3/-1= 1 minus z minusem daje nam plus
2009-12-15T17:43:01+01:00
A) dla x-1 mamy y=2*(1)^2+1=2*1+1=2+1=3

dla x=-1 mamy y=2*(-1)^2+1=2*1+1=2+1=3

b) dla x=1 mamy y=-3(1)^2 =-3

dla x=-1 mamy y=-3(-1)^2= -3

c) dla x=1 mamy y= -3/1= -3

dla x=-1 mamy y= -3/(-1)=3


symbole:
* mnożenie
^potęga
/ dzielenie